INFLUENCE OF ACTIVE ALKALI CHARGE ON DELIGNIFICATON DEGREES AND DEPOLYMERIZATION IN COOKING PROCESS USING KRAFT PULPING METHOD - Bambang Irawan; Vebria Ardina (Journal of International Conference Proceedings (JICP), 2019)
Delignification and depolymerization are the great concerns in the cooking process. This research used manihot esculenta crants, eucalyptus and acacia mangium with active alkali charge of 16% to 20% and 1% variation. Active alkali charge influences degree of delignification and degree of polymerization. Every 1% AA charge increase could increase the degree of delignification in manihot esculenta crants, eucalyptus and acacia mangium of 1.15%, 0.40% and 0.85% respectively. Every 1% AA charge increase could decerase degree of polymerization in manihot esculenta crants, eucalyptus and acacia mangium of 4.14%, 3.32% and 7.04% respectively. The correlations between the degree of delignification and the degree of polymerization in the manihot esculenta crants, eucalyptus and acacia mangium were y(m) = -58,284x + 6392,8, y(e) = -119,74x + 12135 and y(a) = - 149.63x + 14716 respectively.